(untitled) (Journal of Information Technologies in Education (ITE), 2014)
A concept of software support of learning programming language and technologies is regarded in the article. Present systems of independent study of subjects, related to programming, are examined. Necessary components of a system of support learning programming languages and technologies, which is oriented on independent study, are considered.